2015
DOI: 10.1002/hed.24352
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent giant mandibular ameloblastoma in young adults

Abstract: Aggressive resection of the GMA and immediate reconstruction is strongly advised. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1947-E1954, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Although ameloblastoma is one of the most common tumors of the maxillofacial area, a giant ameloblastoma tumor is rare and generally seen in underdeveloped countries and regions [3,4]. Both patients in our report were from rural areas with less education.…”
Section: Discussionmentioning
confidence: 53%
“…Although ameloblastoma is one of the most common tumors of the maxillofacial area, a giant ameloblastoma tumor is rare and generally seen in underdeveloped countries and regions [3,4]. Both patients in our report were from rural areas with less education.…”
Section: Discussionmentioning
confidence: 53%
“…However, this approach leads to severe maxillofacial deformity and results in compromised stomatognathic function, which causes impaired quality of life and psychological distress. Therefore, oral and maxillofacial surgeons are faced with a dilemma between conservative treatment and radical treatment when dealing with patients with ameloblastoma, especially giant ameloblastoma [6]. Some studies have shown that cystic ameloblastoma decreases in size after marsupialization, and the shrinking of tumor bulk makes subsequent surgical treatment easier and less extensive [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Ameloblastoma is a benign but locally aggressive odontogenic epithelial neoplasm that presents as a slowly growing painless swelling of the jaws and accounts for approximately 1% of all mandibular tumors and cysts (1). Although histologically benign, ameloblastoma can be locally destructive, spreading to the base of the skull, paranasal sinuses, infratemporal fossa, pterygopalatine fossa, parapharyngeal space, therefore causing severe facial deformity and functional impairment (2,3).…”
Section: Introductionmentioning
confidence: 99%